METAKOGNISI DALAM PEMBELAJARAN MATEMATIKA - Atma Murni (Jurnal Prinsip Pendidikan Matematika, 2019)
Metacognition is the students’ ability in learning that includes about how learning should be done, so that it can determine what already known and not known yet. Metacognition has two components: metacognitive knowledge and metacognitive skills. Metacognitive knowledge relates to declarative knowledge, procedural knowledge, and conditional knowledge. Metacognitive skills relate to planning, monitoring, and evaluation towards the completion of a particular task. Metacognition has three stages: (1) planning about what, how, and when to learn it; (2) monitoring of learning process that being carried out; and (3) evaluating of what has been planned, done, and the results of that process. Metacognition of students in mathematics learning can be arisen at every stage of mathematical problem solving: understanding the problem, devising a plan, carrying out the plan, and looking back.